PVP-Assisted Hydrothermal Synthesis of Bi2O2Se Nanosheets for Self-Powered Photodetector (Journal of Solar Energy Research Updates, 2022)
Abstract: Bi2O2Se nanosheets were successfully synthesized via a facile one-step PVP-assisted hydrothermal process for the first time. Corresponding characterizations, such as XRD, XPS, SEM and TEM, were carried out to investigate the formation of the products on the amount of PVP in the reaction system. Results revealed that the single-crystalline Bi2O2Se nanosheets with small mean lateral size of 176.3 nm were obtained when the amount of PVP is 0.75 g. Single-crystalline Bi2O2Se nanosheets self-powered photodetector exhibited excellent photodetection performance, superior to that of self-powered photodetectors based on the products synthesized without PVP and other nanomaterials. Under the illumination of 365 nm ultraviolet light, the rise time, responsivity and detectivity could approach up to 9 ms, 14.24 mA/W and 3.16×108 Jones, respectively. Bi2O2Se devices have high photoresponse even in the visible and near infrared bands due to its suitable band gap. The present work provides a novel preparation route of Bi2O2Se via hydrothermal method and PVP assisted synthesis of Bi2O2Se nanosheets is reported for the first time. Bi2O2Se nanosheets self-powered photodetector exhibited excellent photodetection performance and points out a direction for the evolution of self-powered photodetectors in the in the future.